Arbetarpoesin och offentligheterna: Exemplet Stig Sjödin - Nilsson, Magnus (Tidskrift för litteraturvetenskap, 2020)
Working-Class Poetry and Publics: The Example of Stig Sjödin The Swedish poet Stig Sjödin (1917–1993) is generally recognized as an important figure in both Swedish literary history and the history of Swedish working-class literature. This status rests almost exclusively on poetry collections published in the 1940s, 1950s and 1970s. In addition to this, however, Sjödin was also active as a poet within the labour movement. By including his political involvement in the discussion of his poetry collections, this article aims at broadening the understanding of Sjödin’s oeuvre. It also argues that research on modern Swedish workingclass literature must transcend the traditional realm of literature.